THE DEVELOPMENT OF AN ECO EFFECTIVE HOUSING CONCEPT - Jouke Post; Diana van Veldhuizen (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2011)
“Wouldn’t it be great if high-rise blocks simply fell apart when we no longer needthem? Or if an office building turned back to sand and earth once its occupantsmoved to a new commercial estate? We have to get away from the idea that we’re building for eternity.” This idea was the beginning of our lifespan research at the Eindhoven University of Technology in 1990; to develop buildings without waste at the end of their lifetime, was the main focus. During this period we’ve realised buildings with a lifespan of twenty, five and a hundred years. From 1990 till now we’ve made interesting steps. We made the step from sustainability to a more ecological approach. The threat is that buildings are no longer only the result of a brief from the client, but become more and more temporary envelops for their occupant’s business. At a certain point in time no one can or will use this envelope. Therefore it is very important that the used building materials will become part of either a biological or a technological cycle in order for it not to end up as waste.